Generation of contour plan in Malaysia-Indonesia international boundary survey using Carlson Survey 2008 Software [electronic resource] - 372444 Chua, Teng Ket @ Chua Lawrence Linggau (Skudai : Universiti Teknologi Malaysia, 2008)
Project Paper (Sarjana Muda Kejuruteraan (Geomatik)) - Universiti Teknologi Malaysia, 2008